Rat Submandibular Gland Perfusion Method for Clarifying Inhibitory Regulation of GABAA Receptor - Migiwa Okubo; Mitsuru Kawaguchi (Elsevier, 2013)
Abstract.: GABA is an inhibitory transmitter found in rat salivary gland. However, the inhibitory potential of GABA on salivary secretion is unclear. Using an in vivo cannulation method, intraperitoneal administration of GABA was ineffective in the absence of gabaculine, a GABA transaminase inhibitor, on pilocarpine-induced salivary secretion, suggesting that GABA was rendered metabolically inactive before reaching the salivary gland. We hypothesized that the action of a drug on the salivary glands could be measured directly using a submandibular gland perfusion system. The submandibular gland artery, veins, and duct were cannulated in situ so that physiological functions such as innervation would not be compromised. Hank's balanced salt solution (pH 7.4) was perfused at a rate of 0.5 ml/min together with 1 μM carbachol (CCh) over a 5-min period every 30 min. Amount of secreted saliva showed no change to the recurrent addition of CCh to the perfusate. GABA or muscimol dose-dependently inhibited CCh-induced salivary secretion. This effect was blocked by bicuculline, a GABAA-receptor (GABAA-R) antagonist, and enhanced by clonazepam, a central-type benzodiazepine-receptor agonist. These results suggest that salivary secretion is suppressed by GABAA-R in rat salivary gland and that the perfusion method used was effective in clarifying inhibitory regulation of GABAA-R. Keywords:: submandibular gland, perfusion system, xerostomia, γ-aminobutyric acid, salivary secretion